(untitled) (XXI Century. Spanish Literature and Culture, 2013)
This article investigates how Francisco Umbral by way of a “self-portrait” proposes an ontological reflection on his own body and analyses the literary mechanisms of writing about it based on the erotic - understanding the latter more in a creative than a sexual way. By way of this libidinous writing, Mortal y Rosa not only is an autobiography of a personal tragedy but an epistemological study of the deterioration which the body undergoes seen from the many different perspectives of love, paternity, mourning and aging.